Gender differences renin-angiotensin-aldosterone system and its relation to humoral factors in patients with arterial hypertension - G M Dadashova (Системные гипертензии, 2015)
Aim. Explore gender characteristics of the renin-angiotensin-aldosterone system (RAAS), to assess the state of the RAAS relationship with the level of female sex hormones, aldosterone, plasma renin activity in patients with arterial hypertension (AH) in postmenopausal women.Materials and methods. The study included 35 patients with hypertension 1-3-th degree, the average age 56.8±6.9 years. The control group included 21 healthy people with a normal body mass index (BMI). Each of these groups was divided into subgroups by gender: group IA included healthy men (n=10), group IB - healthy women (n=11), group IIA - men with hypertension (n=17), group IIB - Women with hypertension (n=18). Evaluation was carried out with a hormonal status determining levels of estradiol, testosterone, aldosterone, plasma renin activity in the serum.Results. Aldosterone concentration in group IIB was 169.8±109.9 pg/ml and was significantly higher (p